The War Artists’ Advisory Committee, Aviation and the Nation during the Second World War - Rebecca Searle (University of Edinburgh, 2009)
This article draws upon broader research that examines the representation of aviation in the collection of the War Artists’ Advisory Committee (WAAC). On the 23rd November 1939, the WAAC met for the first time. They were charged with creating an artistic record of the war both at home and abroad on behalf of the state. By the time the committee was dissolved in December 1945, it had amassed nearly 6,000 works by over 400 artists, depicting all major aspects of the war. Although library shelves are filled with histories of various aspects of the Second World War, this collection has hardly been touched by academic historians.